Campaign Video Usage in Preventing Cervical Cancer among Female Students - Imam Nuraryo (UIR Press, 2020)
Cervical cancer prevention campaign video contains information ranging from understanding, the symptoms caused to how to avoid cervical cancer. This campaign video is one way to educate the public about the importance of knowing cervical cancer. The purpose of this study was to find out how effective a cervical cancer prevention campaign video on knowledge attitude and intend to behavior among female students. The theory used is Planned Behavior theory which is the result of the refinement of the reasoned action theory developed by Ajzen and Fishbein (1980). The method used is quantitative with the experimental methods. This study used an experimental pre-post-post-test static group design. It could estimate the equivalence of the two groups and have the opportunity to correct differences that have arisen before the event. It must have access to groups before and after events. The controlled group and the experiment group consisted of 15 people per each group. The research data obtained from the questionnaires were processed and analyzed using independent samples t-test. The technique of collecting data by spreading the questionnaire which was distributed into a couple of groups. The result of this research is campaign video does not give a significant effect on knowledge, attitude and behavioral intention of female students neither in the controlled groups nor in experiment group.